Effect of heterologous expression of FT gene from Medicago truncatula in growth and flowering behavior of olive plants - Guerrero, Consuelo; Cerezo, Sergio; Feito, Isabel; Rodríguez, Lucía; Samach, Alon; Mercado, José A.; Pliego-Alfaro, Fernando; Palomo-Ríos, Elena (Frontiers in Plant Science, 2024)
Olive (Olea europaea L. subsp. europaea) is one of the most important crops of the Mediterranean Basin and temperate areas worldwide. Obtaining new olive varieties adapted to climatic changing conditions and to modern agricultural practices, as well as other traits such as biotic and abiotic stress resistance and increased oil quality, is currently required; however, the long juvenile phase, as in most woody plants, is the bottleneck in olive breeding programs. Overexpression of genes encoding the ‘florigen’ Flowering Locus T (FT), can cause the loss of the juvenile phase in many perennials including olives. In this investigation, further characterization of three transgenic olive lines containing an FT encoding gene from Medicago truncatula, MtFTa1, under the 35S CaMV promoter, was carried out. While all three lines flowered under in vitro conditions, one of the lines stopped flowering after acclimatisation. In soil, all three lines exhibited a modified plant architecture; e.g., a continuous branching behaviour and a dwarfing growth habit. Gene expression and hormone content in shoot tips, containing the meristems from which this phenotype emerged, were examined. Higher levels of OeTFL1, a gene encoding the flowering repressor TERMINAL FLOWER 1, correlated with lack of flowering. The branching phenotype correlated with higher content of salicylic acid, indole-3-acetic acid and isopentenyl adenosine, and lower content of abscisic acid. The results obtained confirm that heterologous expression of MtFTa1 in olive induced continuous flowering independently of environmental factors, but also modified plant architecture. These phenotypical changes could be related to the altered hormonal content in transgenic plants.